Genetic Architecture Underlying Response to the Fungal Pathogen Dothistroma septosporum in Lodgepole Pine, Jack Pine, and Their Hybrids - Mengmeng Lu; Nicolas Feau; Brandon Lind; Dragana Obreht Vidakovic; Pooja Singh; Sally N. Aitken; Richard C. Hamelin; Sam Yeaman (Evolutionary Applications)
ABSTRACT In recent decades, Dothistroma needle blight (DNB), a pine tree disease caused by the fungal pathogen Dothistroma septosporum, has severely damaged lodgepole pine (Pinus contorta Dougl. ex. Loud.) in British Columbia, Canada, and raised health concerns for jack pine (Pinus banksiana Lamb.). The pathogen has already shown signs of host shift eastward to the hybrid populations between lodgepole pine and jack pine (Pinus contorta × P. banksiana), and possibly into pure jack pine. However, we have little knowledge about mechanisms of resistance to D. septosporum, especially the underlying genetic basis of variation in pines. In this study, we conducted controlled inoculations to induce infection by D. septosporum and performed a genome‐wide case–control association study with pooled sequencing (pool‐seq) data to dissect the genetic architecture underlying response in lodgepole pine, jack pine, and their hybrids. We identified candidate genes associated with D. septosporum response in lodgepole pine and in hybrid samples. We also assessed genetic structure in hybrid populations and inferred how introgression may affect the distribution of genetic variation involved in D. septosporum response in the studied samples. These results can be used to develop genomic tools to evaluate DNB risk, guide forest management strategies, and potentially select for resistant genotypes.